2019
DOI: 10.1111/birt.12441
|View full text |Cite
|
Sign up to set email alerts
|

The duration of the third stage in relation to postpartum hemorrhage

Abstract: Introduction In this study, we describe the distribution of placenta delivery and the incidence of postpartum hemorrhage in both spontaneous placental delivery and manual removal of the placenta. Methods A retrospective study was performed of 7603 singleton vaginal deliveries of a gestational age over 32 weeks, registered between September 2011 and 2016. We calculated the incidence of postpartum hemorrhage (≥1000 mL blood loss) per 10‐minute duration of the third stage. The odds ratio for developing postpartum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Our study found that a prolonged 3rd stage of labor was associated with an increased risk of severe postpartum hemorrhage. This finding is consistent with previous studies that have reported an increased risk of postpartum hemorrhage with a longer 3rd stage duration of labor [10,17]. Additionally, our study found that an increase in BMI was associated with an increased risk of severe postpartum hemorrhage, which aligns with previous studies reporting obesity as a risk factor for postpartum hemorrhage [19].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study found that a prolonged 3rd stage of labor was associated with an increased risk of severe postpartum hemorrhage. This finding is consistent with previous studies that have reported an increased risk of postpartum hemorrhage with a longer 3rd stage duration of labor [10,17]. Additionally, our study found that an increase in BMI was associated with an increased risk of severe postpartum hemorrhage, which aligns with previous studies reporting obesity as a risk factor for postpartum hemorrhage [19].…”
Section: Discussionsupporting
confidence: 93%
“…In the literature, studies have shown that as the duration of the 3rd stage of labor increases, the amount and risk of postpartum hemorrhage also increase. In a study by Manon Van Ast et al [10] that examined 7,203 single vaginal deliveries, the group with postpartum hemorrhage had a median duration of the 3rd stage of labor of 26 min, while the group without postpartum hemorrhage had a median duration of 10 min. There was a statistically significant difference between these values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation